2018
DOI: 10.1002/slct.201702452
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Complex Supported on Fe3O4@SiO2 Coated by Polyvinyl Alcohol as Reusable Nanocatalyst in N‐Arylation of Amines and N(H)‐ Heterocycles and Green Synthesis of 1H‐Tetrazoles

Abstract: In this paper, copper(II) based catalyst bearing polyvinyl alcohol immobilized on Fe3O4@SiO2 was synthesized and fully characterized by FT‐IR, XRD, TEM, FE‐SEM, DLS, UV‐Vis, XPS, EDX, TGA, VSM, NMR, ICP and elemental analysis techniques. Then, the performance of this magnetic heterogeneous system was investigated in the N‐arylation of nitrogen heterocycles and alkyl amines with aryl halides to produce the desired coupled products in good to excellent yields without using external ligands or additives as promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Catalytic activity of Fe 3 O 4 @MCM-41-SB-Cu is compared with some other catalyst systems reported in the literature for the production of 5-phenyl 1H-tetrazole (Table 4). [33,[66][67][68][69][70][71][72][73][74] The results show that the mentioned magnetic nanocatalyst provides higher yield of the product in shorter reaction time. Furthermore, the catalyst is easily removed from the reaction mixture using an external magnetic field.…”
Section: Catalytic Studymentioning
confidence: 99%
“…Catalytic activity of Fe 3 O 4 @MCM-41-SB-Cu is compared with some other catalyst systems reported in the literature for the production of 5-phenyl 1H-tetrazole (Table 4). [33,[66][67][68][69][70][71][72][73][74] The results show that the mentioned magnetic nanocatalyst provides higher yield of the product in shorter reaction time. Furthermore, the catalyst is easily removed from the reaction mixture using an external magnetic field.…”
Section: Catalytic Studymentioning
confidence: 99%
“…Moreover, the yield of the products was comparable to the previously reported homogeneous systems. [23,[56][57][58][59][60][61] 2 | EXPERIMENTAL…”
Section: Introductionmentioning
confidence: 99%
“…Hamad et al Esmaeilpour et al reported the catalytic use of Fe 3 O 4 @SiO 2 -TCT-PVA-Cu(II) for the N-arylation of N-containing heterocycles such as imidazoles (81a), indoles (81j), pyrrole (106a), piperazine (108e) and N-phenyl piperazines (109d) using aryl halides (82p) as the aryl coupling partner and sodium tert-butoxide as the base in DMF at 100 C in 86-96% yield (Scheme 255). 459 The same protocol was also extended for the synthesis of 5-phenyl 1H-tetrazoles (87c) by the reaction among substituted benzaldehyde (2), sodium azide (66) and hydroxylamine hydrochloride (275) in water under reux via click reaction (Scheme 256). The NPs were prepared by coating Fe 3 O 4 NPs with silica followed by their treatment with (3-chloropropyl)trimethoxysilane and 3-(3-hydroxy-propylamino)-propan-1-ol to obtain NPs having free hydroxyl groups.…”
Section: Bimetallic Np-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%